Development of an electronic radiation oncology patient information management system. - Mandal A; Asthana AK; Aggarwal LM; Mandal, Abhijit; Asthana, Anupam Kumar; Aggarwal, Lalit Mohan (Journal of Cancer Research & Therapeutics)
The quality of patient care is critically influenced by the availability of accurate information and its efficient management. Radiation oncology consists of many information components, for example there may be information related to the patient (e.g., profile, disease site, stage, etc.), to people (radiation oncologists, radiological physicists, technologists, etc.), and to equipment (diagnostic, planning, treatment, etc.). These different data must be integrated. A comprehensive information management system is essential for efficient storage and retrieval of the enormous amounts of information. A radiation therapy patient information system (RTPIS) has been developed using open source software. PHP and JAVA script was used as the programming languages, MySQL as the database, and HTML and CSF as the design tool. This system utilizes typical web browsing technology using a WAMP5 server. Any user having a unique user ID and password can access this RTPIS. The user ID and password is issued separately to each individual according to the person's job responsibilities and accountability, so that users will be able to only access data that is related to their job responsibilities. With this system authentic users will be able to use a simple web browsing procedure to gain instant access. All types of users in the radiation oncology department should find it user-friendly. The maintenance of the system will not require large human resources or space. The file storage and retrieval process would be be satisfactory, unique, uniform, and easily accessible with adequate data protection. There will be very little possibility of unauthorized handling with this system. There will also be minimal risk of loss or accidental destruction of information.